Biometrics Technology based Mobile Voting Machine - Ghatol, Prajakta S; Mahale, Neelam (International Journal of Computer Sciences and Engineering, 2014)
The Voting process is heart of democracy and India is largest democracy in the world where every citizen above 18 years has right to vote. For good democracy, a voting system should be correct, transparent and fully authentic. Biometrics technology is very advanced and more accurate in secure and feasible authentication to the voters. The proposed voting system is mainly for those people who are not capable to come to the voting booth. This electronic voting machine is more secured and better than exiting voting process. The advancement in wireless and web technologies given rise to the new applications in e-Government services such as online tax filing, license renewal, and benefits claims. The proposed work uses android mobile OS to develop an application and fingerprint supported biometric control information to make voting process more secure. Using android smart mobile device makes the system even more robust.